The question of school language in multilingual societies: the example of Ghana - Samuel Opoku Appiah; Alfredo Ardila (Peoples' Friendship University of Russia (RUDN University), 2020)
The language used in school represents a crucial and polemic question in multilingual societies. Sub-Saharan Africa represents a world region with a significant linguistic diversity. Until recently, most of these countries were European colonies. During colonial times, the colonizer language generally dominated in schools. After their independence, many countries have continued using that language as the instructional language. It is observed that quite often, children are schooled in a second language, and teachers must teach in a foreign language. This situation results in potentially negative consequences affecting school learning. The specific example of Ghana is examined. It is pointed out that in Ghana during recent years frequent changes have been introduced in school language. Commonly, English is used as the primary school language. Because this association between language and school learning, speaking English provides not only significant social prestige, but also results in better working opportunities. The question of so-called "international schools" in Ghana is also examined; most of these schools do not teach any of the Ghanaian languages, but a foreign language, such as French, Spanish, or Portuguese. It is argued that these international schools may have adverse consequences on Ghanaian children who attend them. Ghana, however, has been a strong advocate of the so-called "African personality" and the use of English as the medium of instruction is in overt opposition to this ideology. It is concluded that children schooled in a second language, and teachers teaching in language that they do not master well enough may represent a potential barrier for the social, scientific, and economic development of sub-Saharan African countries, such as Ghana.